Ageing, Drosophila melanogaster and Epigenetics. - Halim, M.A.; Tan, F.H.P.; Azlan, A.; Rasyid, I.I.; Rosli, N.; Shamsuddin, S.; Azzam, G. (The Malaysian journal of medical sciences, 2020)
Ageing is a phenomenon where the accumulation of all the stresses that alter the functions of living organisms, halter them from maintaining their physiological balance and eventually lead to death. The emergence of epigenetic tremendously contributed to the knowledge of ageing. Epigenetic changes in cells or tissues like deoxyribonucleic acid (DNA) methylation, modification of histone proteins, transcriptional modification and also the involvement of non-coding DNA has been documented to be associated with ageing. In order to study ageing, scientists have taken advantage of several potential organisms to aid them in their study. Drosophila melanogaster has been an essential model in establishing current understanding of the mechanism of ageing as they possess several advantages over other competitors like having homologues to more than 75% of human disease genes, having 50% of Drosophila genes are homologues to human genes and most importantly they are genetically amenable. Here, we would like to summarise the extant knowledge about ageing and epigenetic process and the role of Drosophila as an ideal model to study epigenetics in association with ageing process.